Development of Digital Interactive Board-Based Learning as a Solution for Elementary School Science Learning - Nofa Arista; Enny Susiyawati; Binar Kurnia Prahani (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: This study aimed to develop a Digital Interactive Board-Based Learning system as an innovative instructional medium for elementary science education and to evaluate its validity, practicality, and effectiveness. Method: This study employed a Research and Development (R&D) approach using the ADDIE model, which consists of the Analysis, Design, Development, Implementation, and Evaluation phases. Subject matter experts, instructional media experts, and instructional design experts evaluated product validity. At the same time, practicality and effectiveness were assessed through classroom implementation involving elementary school students using observation sheets, response questionnaires, and learning achievement tests. Results: The validation results indicated that all evaluation aspects achieved the very valid category, with an overall average score of 95.21%. The N-Gain value of 0.69 indicates a moderate-to-high level of learning improvement, demonstrating that the implementation of the Digital Interactive Board-Based Learning (DI-BBL) system significantly enhanced students' conceptual understanding of science. The findings demonstrated that the developed learning system achieved very high levels of validity, practicality, and effectiveness, significantly improving students' learning engagement, conceptual understanding, and critical thinking skills in science learning. Novelty: The novelty of this study lies in the development of an integrated Digital Interactive Board-Based Learning system that combines interactive multimedia, inquiry-based exploration, digital assessment, immediate feedback, and reflective learning within a single instructional environment, thereby supporting the implementation of the Merdeka Curriculum and fostering twenty-first-century competencies among elementary school students.